Targeted metabolome analysis reveals accumulation of metabolites in testa of four peanut germplasms - Zhang, Kun; Ma, Jing; Gangurde, Sunil S.; Hou, Lei; Xia, Han; Li, Nana; Pan, Jiaowen; Tian, Ruizheng; Huang, Huailing; Wang, Xingjun; Zhang, Yindong; Zhao, Chuanzhi (Frontiers in Plant Science, 2022)
Cultivated peanut (Arachis hypogaea L.) is an important source of edible oil and protein. Peanut testa (seed coat) provides protection for seeds and serves as a carrier for diversity metabolites necessary for human health. There is significant diversity available for testa color in peanut germplasms. However, the kinds and type of metabolites in peanut testa has not been comprehensively investigated. In this study, we performed metabolite profiling using UPLC-MS/MS for four peanut germplasm lines with different testa colors, including pink, purple, red and white. A total of 85 metabolites were identified in four peanuts. Comparative metabolomics analysis identified 78 differentially accumulated metabolites (DAMs). Some metabolites showed significant correlation with other metabolites. For instance, proanthocyanidins were positively correlated with cyanidin 3-O-rutinoside and malvin, and negatively correlated with pelargonidin-3-glucoside. We observed that the total proanthocyanidins are most abundant in pink peanut variety WH10. The red testa accumulated more isoflavones, flavonols and anthocyanidins compared with that in pink testa. These results provided valuable information about differential accumulation of metabolites in testa with different color, which are helpful for further investigation of the molecular mechanism underlying biosynthesis and accumulation of these metabolites in peanut.